Anatomy of post-communist European defense institutions: The mirage of military modernity - Jordaan, Evert (Scientia Militaria - South African Journal of Military Studies, 2020)
In Anatomy of post-communist European defense institutions: The mirage of military modernity, Thomas-Durell Young’s aim was to determine why Central and Eastern European (CEE) states have failed to apply democratic defence governance concepts, despite 25 years of Western assistance programmes.